Sengketa Subsidi Antara Airbus Dengan Boeing di WTO - , JONI EKO PRAMONO, Dr. Poppy S. Winanti. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As major player in Aircraft Industries, both Airbus and Boeing are at constant war over subsidies. These conflict goes to a whole new level when United States decided to bring this conflict to the WTO in 2004 by filling a complaint over subsidy to the Airbus by European Union, which responded by European Union by asking a parallel investigation to the WTO over subsidy from United states to Boeing. This Paper aim to understand the process of the dispute from the WTO Dispute Settlement Body.